Caracterização morfodinâmica e morfoestrutural do astroblema de Vista Alegre - Coronel Vivida - Paraná - Coelho, Manoela Gomes dos Anjos (2015)
Meteorite impact craters commonly found on the surface of some planets and the Moon need some diagnostic features for its determination. Dated thousands or millions of years, these structures besides presenting typology/ differentiated morphology of other relevant features, have been obliterated over geological time through the action of geological processes, soil, bioclimatic, etc., may be they can come to be erroneously classified within a regional geomorphological analysis and/ or location due to no knowledge of these diagnostic features. Thus, this paper presents a characterization of astrobleme area of Vista Alegre, located in the city of Coronel Vivida, southwest of Paraná state. Identified the origin of the structure, we proceeded to the characterization of geological and geomorphological context of modeling, where there was regional structures clearly influenced by astrobleme, evidenced in deformation of lithostructure and in the presence of the guidelines, especially the positive presenting displaced crests forming parallel systems, while other guidelines have bends in the opposite direction to the crater, forming fault systems with standard components and transcurrent. The tholeiitic basalts occupy adjacent areas and much of the astrobleme structure, but there is also the presence of polymict breccias and diagnostic features of this type of printed structure in these lithologies. Also identified forms of individual relief features of the modeled dissection and accumulation by photo-interpretation of aerial photographs, thus defining the three geomorphological units set to Geomorphological Domain Summit Borders, Geomorphologic Domain of Low Hills and Geomorphologic Domain Central depression. This draina ge system is superimposed, commanded by river Chopim and is responsible for the erosion of the southwestern part of astrobleme, presenting dendritic drainage patterns and centripetal radial and drainage density difference between the periphery and the cent er of astrobleme. Soils were identified with indigenous and clay, but also the presence of Quaternary sedimentary deposits of fluvial origin, colluvial and alluvial-colluvial undifferentiated with detection of subsurface structures by Georradar. The morphostructural characterization of astrobleme and surrounding areas was performed by mapping the guidelines from the drainage network and photo interpretation, while setting the preferred direction of fluvial channels first order due to local drainage is conditioned to likely failures. In addition, we present a proposal of morphogenetic evolution model astrobleme, whose evolution is associated with the differential erosion in blocks failed/slaughtered originated in the process of forming the edges initially we athering phases responsible for the emergence of planning surfaces through erosion side and, in humid climates, pedogenesis processes, colluvial deposition and current modeling this crater.